Application of Platelet Rich Fibrin in Tissue Engineering: Focus on Bone Regeneration. (17th February 2021) - Farmani, Ahmad Reza; Nekoofar, Mohammad Hossein; Ebrahimi Barough, Somayeh; Azami, Mahmoud; Rezaei, Nima; Najafipour, Sohrab; Ai, Jafar
Abstract: Bone tissue engineering (BTE) is a strategy for reconstructing bone lesions, which is rapidly developing in response to higher demands for bone repairing. Recently, this method, along with the emergence of functionally graded, biocompatible and biodegradable materials, has been expanded. Moreover, scaffolds with chemical, physical and external patterns have induced bone regeneration. However, the maintenance of healthy bone and its regeneration in the human body needs a series of complex and accurate processes. Hence, many studies have been accompanied for reconstructing bone by using blood-derived biomaterials, especially platelet-rich fabricates. The most important reason for using platelet-rich formulations in bone regeneration is based on releasing growth factors from alpha granules in platelets, which can induce osteogenesis. Moreover, the presence of fibrin nano-fiber structures as a constituent can provide a good substrate for cell attachments. This study attempts to review the history, structure, and biology of platelet-rich fibrin (PRF) as well as in vitro, pre-clinical, and clinical studies on the use of PRF for bone regeneration.